2021
DOI: 10.1029/2020jd033822
|View full text |Cite
|
Sign up to set email alerts
|

Migrating Semidiurnal Tide During the September Equinox Transition in the Northern Hemisphere

Abstract: Specified Dynamics Whole Atmosphere Community Climate Model with thermosphere‐ionosphere eXtension simulations are used to investigate the solar migrating semidiurnal tide (SW2) around September equinox at middle to high latitudes in the Northern Hemisphere. A pronounced minimum in SW2 occurs around September equinox, and is characterized by a ∼50% reduction in tidal amplitudes for 20–30 days. Analysis of the simulation results indicates that the SW2 minimum occurs due to the seasonal transition of the zonal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 62 publications
(71 reference statements)
2
12
0
Order By: Relevance
“…This is confirmed in Figure 9 of Pedatella et al. (2021), who analyzed Specified Dynamics Whole Atmosphere Community Climate Model with thermosphere‐ionosphere eXtension (SD‐WACCMX) simulations. In addition, Conte et al.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 61%
See 1 more Smart Citation
“…This is confirmed in Figure 9 of Pedatella et al. (2021), who analyzed Specified Dynamics Whole Atmosphere Community Climate Model with thermosphere‐ionosphere eXtension (SD‐WACCMX) simulations. In addition, Conte et al.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 61%
“…Even though the wind reversal time in Figure 3a corresponds to mesospheric altitudes, it is reasonable to expect it to occur some days earlier than at stratospheric altitudes. This is confirmed in Figure 9 of Pedatella et al (2021), who analyzed Specified Dynamics Whole Atmosphere Community Climate Model with thermosphere-ionosphere eXtension (SD-WACCMX) simulations. In addition, Conte et al (2018) reported that meteor radar observations show an increase in gravity wave activity during the fall equinox.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 57%
“…While the transition from predominant semidiurnal to diurnal tide also takes place at and around 110 km altitude, there is an upper band of strong semidiurnal oscillations especially during the first half of September. This apparent weakening of the upper 12 hr band around equinox is an important feature since atmospherically forced semidiurnal tides have been shown to undergo such an autumn transition (Pedatella et al, 2021). Whether this upper band is generated in situ or forced by some atmospheric tidal mode that propagates unusually far up remains to be investigated in more detail.…”
Section: Neutral Windmentioning
confidence: 99%
“…The numerical study of the SW2 tide has a long history (e.g., Forbes & Garrett, 1979). Nevertheless, open questions remain about the mechanisms governing the tide's seasonal and short‐term variability (Conte et al., 2018; G. Liu et al., 2021; Pedatella et al., 2020; Zhang et al., 2021). Many recent studies are in part driven by the increasing availability of high‐altitude and tide‐resolving general circulation models.…”
Section: Introductionmentioning
confidence: 99%